Teacher Barriers in Utilizing Google Meet in Speaking Class - Inayatillah, Iin; Rachmawati, Etika; Tarwana, Wawan (Journal of English Education Program (JEEP), 2024)
E-learning developments are almost relevant with the use of current famous learning technology like Google Meet which can be recommended to build communication between teachers and students. This research was carried out to find out how the teacher utilizes Google Meet and reveals the teacher’s barriers to practicing Google Meet in speaking class. This research adopted a qualitative case study and with online classroom observation and semi-structured interviews as the instruments of the study. Research participants embraced in this research were an English teacher and fifteen students of class 1B in the first semester of an English education department at a University in Ciamis. In processing the data of online classroom observation, the researcher classified and interpreted the classroom observation data. Then, the interview data were transcribed, translated it into English, analyzed, interpreted, and concluded. The findings showed that there were three key elements of the present research. First, Google Meet is beneficial in online learning. Second, Google Meet provided several advanced features that were simple to use. Third, the teacher had some troubles in using Google Meet including bad internet connection, student’ gadget error, and students’ distracted in learning.